Questionner les traces d'activités en ligne pour mieux comprendre l'expérience d'apprentissage des étudiants - Karim Boumazguida; Gaëtan Temperman; Bruno De Lièvre
This study examines learning on a SPOC accessible on the Moodle online learning platform. Exploitation of the traces of learning activities and a post-test (on paper) are allowing to objectify degree of control achieved.It highlights that several variables related to learners' online activities would explain their mastery at the end of learning.We observe that watching video (informative task), self-evaluation (formative task) and reformulation of the content in forums (interactive tasks) may explain success factors of learners. A cluster approach gives rise of a typology of learners in a SPOC device : the « observer participants », the « passive participants » and finally the « active participants ». Opinion of students goes in the same vein.